2006
DOI: 10.1021/ef060080d
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Molecular Diffusion Coefficients of Carbon Dioxide, Methane, and Propane in Heavy Oil under Reservoir Conditions

Abstract: R e p r o d u c e d with p e r m issio n o f th e co p y r ig h t o w n e r . F u rth er rep ro d u ctio n p roh ib ited w ith o u t p e r m issio n .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 20 publications
10
95
0
1
Order By: Relevance
“…The propane molecular diffusion coefficient in this heavy oil, D = 7.9 × 10 −6 cm 2 /s at T = 23.9 • C, was obtained by using the pressure decay method (Tharanivasan et al 2006). In addition, the apparent propane molecular diffusion coefficient as defined in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The propane molecular diffusion coefficient in this heavy oil, D = 7.9 × 10 −6 cm 2 /s at T = 23.9 • C, was obtained by using the pressure decay method (Tharanivasan et al 2006). In addition, the apparent propane molecular diffusion coefficient as defined in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, there are a series of helical mixing units within a cylindrical tube. Though fluid mixing process is the process of molecular diffusion, it can still be subdivided into following three categories according to the *Corresponding author, E-mail: hudedong@126.com mechanism: the main convection, vortex movement and molecular diffusion [14][15][16]. The fluid flows through the mixing unit will form radial velocity, main convection and vortex movement, so the fluids will be mixed uniformly.…”
Section: The Structure Design Of Gas Mixermentioning
confidence: 99%
“…Comparing with other optimization methods, Genetic Algorithm has the advantage of global searching and escaping from a local optimization. The objective function used to guide the optimization process is the same as the one used by Tharanivasan et al [22]:…”
Section: Theorymentioning
confidence: 99%
“…x H 2 S = −0.0148T + 6.7255 R 2 = 0.9965 (22) Later on, Marriott et al [9] showed that the terms at the left hand side of Eqs. (4) and (5) were independent of the headspace H 2 S partial pressure.…”
Section: Numerical Optimizationmentioning
confidence: 99%